Teen pregnancy: Overview of the causes and its effects on the education of girls' child - Odiri E Onoshakpokaiye; Eloho Anthonia, Oboawharhe (ILIN Institute, 2023)
The study's objective is to examine teenage pregnancies, including an overview of some of the causes and their effects on the education of girl children. The study uses a descriptive methodology. 200 teenage pregnant students from secondary schools were chosen at random for the study. To direct the study that led to the result, three research questions were stated. Data were gathered for the study using an interview and a questionnaire. Using a benchmark of 2.50, conclusions were drawn from the descriptive data. According to the research's conclusions, teen pregnancy is influenced by parental social economic position, students' exposure to sexual media content, and peers or friends. Additionally, certain recommendations were made.